An analysis of caregiver profile and its impact on employment situation: Primary caregivers of patients of Alzheimer's and other dementias in the South Western of Spain - Manuel Ruiz-Adame Reina; M. Carmen González-Camacho; Alfredo Mainar-Causapé (Atlantic Review of Economics, 2015)
The aim of this paper is to analyse the main demographic and socio-economic conditions of the primary caregivers of Alzheimer's and dementia sufferers, and their relationship to the employment situation of the caregiver. Material and Methods: Empirical analysis of the data obtained from surveys of 694 primary caregivers of Alzheimer's and dementia sufferers through the Andalusian Associations of Relatives of Alzheimer's Patients. The sampling procedure was selective non-probabilistic sampling. The SPSS 19 statistical software package was used to process the data. The verification of the hypothesis of independence of variables was performed using the chi square test under the usual parameters. Results: The employment rate of working-age caregivers is much lower than that of the general population, especially in older women with low levels of education who live with the patient. The data revealed that caregiving which takes place in the home represents the main restriction preventing access to the labour market, i.e. living with the patient is an additional handicap, and an even greater one for women. Conclusions: Those who care for dementia patients have greater limitations in accessing the labour market than the rest of the population, and this limitation is significantly greater when care is provided in the home. As such, health and social policy, with a view towards encouraging employment, needs to take into account the option of boosting available resources outside of family care.
Keywords: I10; I13; J7; 330; Informal care; Caregivers; Dementia; Employment; Public Health